Occurrence of extended- spectrum β-lactamases and ertapenem- mono- resistance in Escherichia coli isolated from diarrheal calves - Lívia Karahutová; Dobroslava Bujňáková (One Health, 2025)
The rise of antimicrobial resistance, particularly against last-resort antibiotics, is a major global health challenge. To address this crisis, implementation of the One Health concept, including surveillance across the environment, public and veterinary health sectors is strongly recommended. This study aimed to assess the antibiotic resistance of Escherichia coli strains isolated from faeces of diarrheal calves on eight farms in eastern Slovakia. We particularly focused on isolates carrying extended-spectrum beta-lactamases (ESBL), carbapenemases, fluoroquinolone resistance, and mobile colistin resistance genes.High resistance rates were observed for penicillins (ampicillin: 76 %; ampicillin + sulbactam: 50 %) and tetracycline (73 %), followed by quinolones (54 %), sulphonamides (46 %), aminoglycosides (tobramycin: 29 %; gentamicin: 44 %), and second and third generation cephalosporins (cefuroxime: 29 %; cefotaxime + clavulanic acid: 1 %; cefotaxime: 22 %). Sporadic resistance to fourth generation cephalosporins (2 %) and ertapenem mono-resistance (5 %) was also noted. Multidrug resistance (MDR) was observed in 71 % of the isolates. Automated interpretative reading of the antibiogram revealed six resistance mechanisms. The most concerning was the CTX-M type ESBL, with confirmed presence of the blaCTX-M-1, blaCTX-M-2, and blaCTX-M-9 genes, along with MDR and mobile gene elements (int1 and tn3), which facilitate the horizontal spread of resistance genes. Additionally, two blaCMY-2-positive isolates were observed with the int1 and tn3 genes. Genes responsible for resistance to other antimicrobial classes (such as tetracyclines, fluoroquinolones, and aminoglycosides) were also detected.Our results suggest that calves may serve as a reservoir for MDR, ESBL/AmpC, and ertapenem-mono-resistant strains of E. coli, posing a potential public health risk through the horizontal spread of resistance genes.